2017
DOI: 10.1136/bcr-2016-218808
|View full text |Cite
|
Sign up to set email alerts
|

Limited cutaneous systemic sclerosis arising in a patient with Graves’ disease

Abstract: Although Graves' disease and systemic sclerosis are both autoimmune disorders, their relationship is rarely reported. We present the case of a Filipino woman with goitre and thyrotoxic signs and symptoms. Diagnosed with Graves' disease at the outpatient clinic, she took antithyroid medications and underwent radioactive iodine ablation with resultant hypothyroidism after 6 months, during which she began to experience skin tightness over the face, neck and fingers. Workup revealed limited cutaneous systemic scle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…This is because RP has been reported in patients with hypothyroidism and symptoms disappeared after thyroid replacement therapy 22,23 . RP with Graves' disease has been reported as a presentation of lcSSc for many years before lcSSc was diagnosed 24 . Withrington et al also reported a patient with a diagnosis of mixed connective tissue disease and that RP developed hypothyroidism 15 months later 25 .…”
Section: Discussionmentioning
confidence: 99%
“…This is because RP has been reported in patients with hypothyroidism and symptoms disappeared after thyroid replacement therapy 22,23 . RP with Graves' disease has been reported as a presentation of lcSSc for many years before lcSSc was diagnosed 24 . Withrington et al also reported a patient with a diagnosis of mixed connective tissue disease and that RP developed hypothyroidism 15 months later 25 .…”
Section: Discussionmentioning
confidence: 99%